Implementasi Model Pendidikan Lingkungan UNESCO Di Sekolah Dasar - Ni Kadek Supadmini; I Komang Wisnu Budi Wijaya; Ida Ayu Diah Larashanti (Cetta: Jurnal Ilmu Pendidikan, 2020)
Human and the environment have an interdependence relationship. The human survival is depends on the environmental condition and vise versa. In fact, the degradation of environmental quality is mostly happen due to human activities. Therefore, it is necessary to apply the environmental education since primary school age. UNESCO has developed the environmental education model consists of three conceptual, they are education about the environment, education in the environment and education for the environment. This UNESCO environmental education development model is suitable to be applied in primary school for inside or outside classroom activities. The teacher’s role in implementing the environmental education model is as a model, motivator, developer and evaluator.